How did SCHIP affect the insurance coverage of immigrant children? - Buchmueller, Thomas C. 1963-; LoSasso, Anthony; Wong, Kathleen (Working paper series / National Bureau of Economic Research, 2007)
The State Children's Health Insurance Program (SCHIP) significantly expanded public insurance eligibility and coverage for children in "working poor" families. Despite this success, it is estimated that over 6 million children who are eligible for public insurance remain uninsured. An important first step for designing strategies to increase enrollment of eligible but uninsured children is to determine how the take-up of public coverage varies within the population. Because of their low rates of insurance coverage and unique enrollment barriers, children of immigrants are an especially important group to consider. We compare the effect of SCHIP eligibility on the insurance coverage of children of foreign-born and native-born parents. In contrast to research on the earlier Medicaid expansions, we find similar take-up rates for the two groups. This suggests that state outreach strategies were not only effective at increasing take-up overall, but were successful in reducing disparities in access to coverage.